One fox a counting book thriller - Read, Kate 1978- (Two Hoots, 2020)
"One famished fox with two sly eyes is on the prowl . . . three plump hens had better watch out! The rich, close-up illustrations take the reader to the heart of the drama in this exciting story set in a moonlit farmyard. With something different to count in every picture, learning numbers from one to ten has never been so much fun, while the story will keep everyone gripped to the last, hugely satisfying page."--Publisher